Improved Biogas Production Sytem And Method Of Manufacture Thereof - KRUEGER JEFFREY TREY (2018)
The present invention provides a biogas production system comprising: at least one digester for generating biogas and digestate, each digester comprising: a first end portion, a second end portion, and a peripheral side-wall there-between; one or more inlets, wherein at least one inlet is arranged to receive organic substrates; one or more outlets, wherein at least one outlet is arranged to release biogas; and a feed system comprising a pit arranged to receive and supply said organic substrates to the digester, said inlet positioned adjacent to a lower portion of said pit, the pit arranged such that a weight of the organic substrates within the pit bias the organic substrates into the digester. 本发明提供种生物气体生产系统，其包括：至少个用于产生生物气体和沼渣的消化池，以及进料系统。每个消化池包括：第端部，第二端部，以及在两者之间的周边侧壁；个或多个入口，其中至少个入口设置成接收有机底物；个或多个出口，其中至少个出口设置成释放生物气体。所述进料系统包括设置成将所述有机底物接收并供应到消化池的凹坑，所述入口设置为邻近所述凹坑的下部，所述凹坑设置成使得在凹坑内的有机底物的重量将有机底物偏斜至消化池中。